Emotional intelligence and caring behavior among Iranian nurses - Atefe Fallah; Mohsen Adib-Hajbaghery; Mahdieh Sabery; Yasaman Raddadi (Kashan University of Medical Sciences, 2023)
Background: Several studies in Iran have examined nurses' caring behaviors (CB) or emotional intelligence (EI). However, no study in Iran investigated the relationship between EI and CB among Iranian nurses.Objectives: This study examined the correlation between EI and CB among nurses.Methods: A cross-sectional study was conducted in 2020 on a sample of 223 nurses working in Shahid-Beheshti Hospital in Kashan, Iran. A demographic questionnaire, the Caring Dimension Inventory-25, and the Siberia Schering's EI questionnaire were used to collect data. Descriptive statistics, t-test, one-way analysis of variance, and Pearson's correlation coefficient were used to analyze the data.Results: Totally, 202 nurses completed and returned the study questionnaires. Most of the nurses were female (66.8%), married (77.2%), and had a bachelor's degree in nursing (84.7%). The mean age and work experience of the participants were 31.17±6.59 and 2.11±2.06 years, respectively. The mean EI and CB scores of the nurses were 100±17.99 and 43.87±10.14, respectively. Although no significant correlation was found between the nurses' overall CB and EI scores (r=0.065, p=0.358), a significant correlation was found between the scores of "psychosocial care" subscale and all components of EI.Conclusion: Nurses demonstrated moderate EI and low CB. A significant relationship was observed between the scores of psychosocial caring behaviors with the total score of EI and its dimensions. It is suggested to design and implement programs to promote nurses' EI. Hope that these programs will improve CB in nurses.